2017
DOI: 10.1016/j.amsu.2017.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, characteristics and outcomes of appendicular neuroendocrine tumors: A cross-sectional study from an academic tertiary care hospital

Abstract: BackgroundAppendicular neuroendocrine tumors (NET, Carcinoid tumors) of the appendix are rare and mostly diagnosed incidentally on the post-operative histopathological examination. NET are usually associated with good 5-year survival rates. We aimed to assess our experience for the diagnosis and management of NET over 11 years.MethodIt is a retrospective chart review of all clinically suspected patients with acute appendicitis who underwent emergent appendectomy with intention to treat between January 2004–Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 21 publications
3
18
1
1
Order By: Relevance
“…In our cohort, majority of tumours were located in body and base of appendix (54.5%). This is contrary to other studies, where over 90 % of ANEN are located at the tip of appendix (14) However, our study corresponds with other studies, where over 80% of neuroendocrine neoplasms are well differentiated (14).…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…In our cohort, majority of tumours were located in body and base of appendix (54.5%). This is contrary to other studies, where over 90 % of ANEN are located at the tip of appendix (14) However, our study corresponds with other studies, where over 80% of neuroendocrine neoplasms are well differentiated (14).…”
Section: Discussioncontrasting
confidence: 98%
“…Incidence of incidental ANET was 0.70% in our series. This corresponds to other studies, where incidence was 0.08% to 1.6% (11)(12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Most carcinoid tumors are located at the tip of the appendix, and they are usually less than1 cm but rarely larger than 2 cm in diameter. [1,2] In the present study, we reported a series of 12 appendiceal carcinoid tumors detected after emergency appendectomy at our clinic.…”
Section: Introductionmentioning
confidence: 86%
“…[1][2][3][4][5][6] However, the overall incidence remains low; found in as few as 0.3-0.9% appendicectomy specimens. [3][4][5][6][7][8] Almost all appendiceal carcinoids are found incidentally on appendicectomy, and rarely are diagnosed before surgery for suspected appendicitis. [3][4][5][6]8,9 Appendiceal carcinoids typically behave in a benign manner and metastases are uncommon.…”
Section: Introductionmentioning
confidence: 99%